2022
DOI: 10.1021/acsomega.2c01470
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the Detailed Structure–Activity Relationships of Isatin and Their Isomers As Monoamine Oxidase Inhibitors

Abstract: Monoamine oxidase (MAO) is a protein with a key function in the catabolism of neuroamines in both central and peripheral parts of the body. MAO-A and -B are two isozymes of this enzyme which have emerged to be considered as a drug target for the treatment of neurodenerative disorders such as Alzheimer’s disease (AD) and Parkinson’s disease (PD). Isatin is an endogenous small fragment, reversible inhibitor for MAO enzymes and is more selective for MAO-B than -A. Isatin is responsible for increasing the dopamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 60 publications
1
21
0
Order By: Relevance
“…There are two isoforms of MAO (MAO-A and MAO-B). , The MAO-A inhibitor moclobemide is a moderately effective antidepressant drug, and the MAO-B inhibitors selegiline and resagiline are globally approved treatments for Parkinson’s disease . Kumar et al reported the structure–activity relationships for MAO-A and -B inhibitors . In this report, isoindoline 1,3-dione, which shares a common structure with isoindolinones, and phthalide derivatives were evaluated.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are two isoforms of MAO (MAO-A and MAO-B). , The MAO-A inhibitor moclobemide is a moderately effective antidepressant drug, and the MAO-B inhibitors selegiline and resagiline are globally approved treatments for Parkinson’s disease . Kumar et al reported the structure–activity relationships for MAO-A and -B inhibitors . In this report, isoindoline 1,3-dione, which shares a common structure with isoindolinones, and phthalide derivatives were evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…In this report, isoindoline 1,3-dione, which shares a common structure with isoindolinones, and phthalide derivatives were evaluated. Substitution at C-5 of isoindoline 1,3-dione or phthalides increased the inhibitory activity of MAO-A and MAO-B . Thus, isoindolinones and phthalides isolated from Xylariaceae may show MAO inhibitory activity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Isatin (1 H ‐indoline‐2,3‐dione) and many of its derivatives exhibit a broad spectrum of biological activities, including activity on the CNS and in chemotherapy [12] . Some of the biological activities of isatin‐ring‐containing derivatives commonly mentioned in references include anticonvulsants, [13] sedatives and hypnosis, [14] monoamine oxidase inhibitors, [12a] antiviral, [15] antioxidant, [16] anticancer, [17] anti‐mycobacterial, [18] and antibacterial activity, [19] etc. Additionally, several derivatives of isatin have been synthesized and probed for inhibitory activity of AChE and BChE enzymes, [20] including hydrazones [21] and (thio)semicarbazones [22] .…”
Section: Introductionmentioning
confidence: 99%